ANALISA BEBAN KERJA FISIK SEBAGAI DASAR PENENTUAN WAKTU ISTIRAHAT YANG OPTIMAL (Studi Kasus Di PT. X) - Rizki Nur Annisa; Tutik Farihah (UIN Sunan Kalijaga Yogyakarta, 2018)
Workload can be defined as difference between the capacity or ability and the amount of work in specified periods. This research at PT. X in the printing and lathe jobs which exposed to environmental factors to identify and evaluate the workload of employees on the job of printing and lathe based on the pulse and the optimal rest time. The method of this research is physiological approach using measurement data of pulse and physical data of respondent to calculate %CVL, energy consumption level, and optimal rest time. The results obtained that workload significant with work environment factors(independent t test) with %CVL 33.67% for lathe and for %CVL 21.21% for printing unit. Based on paired T test the significant , working pulse significantly difference with resting pulse with 35.60 beats/ min working pulse for lathe and 23.95 beats/min for printing. Optimal rest time through calculation of energy consumption is 217.79 minutes for lathe unit and 98.69 minutes for printing unit.